Membangun Critical Thinking Mahasiswa Program Studi Pendidikan Agama Hindu Melalui Problem Based Learning Pada Mata Kuliah Profesi Pendidikan Dan Keguruan - Putu Cory Candra Yhani; I Gede Dharman Gunawan; Putu Wisnu Saputra; I Komang Mertayasa (Satya Sastraharing : Jurnal Manajemen, 2024)
Critical thinking skills are very important for students, especially for students studying in the Hindu Religious Education Study Program. As prospective educators, students are required to be able to analyze situations, evaluate various options, and create innovative solutions that are relevant to solving problems that arise, both in the academic and social fields. Building critical thinking aims to identify and understand the implicit assumptions underlying an argument, thereby increasing students' capacity to adapt to cultural and value diversity. For students of the Hindu Religious Education Study Program, this critical thinking ability is crucial, because they are required to be able to integrate Hindu spiritual values ​​with the challenges of education in a multicultural era. The application of PBL in Professional Education and Teaching courses also supports the formation of student character as prospective educators who are professional and have integrity. Implementation of PBL by building critical thinking in the Education and Teaching Professionals course, which is one of the relevant courses for developing critical thinking skills. This course requires students to understand the role of teachers as agents of change who are able to provide solutions to educational problems in the modern era. Apart from that, this course also provides students with insight into the importance of professionalism and ethical responsibility in the teaching profession.